2003
DOI: 10.1080/00016470310018171
|View full text |Cite
|
Sign up to set email alerts
|

Tranexamic acid reduces blood loss and blood transfusions in primary total hip arthroplastyA prospective randomized double-blind study in 40 patients

Abstract: Transemic acid is effective in reducing the postoperative blood loss, the total blood loss and the need for blood transfusion in primary total hip arthroplasty.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
85
3
4

Year Published

2004
2004
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 138 publications
(94 citation statements)
references
References 9 publications
2
85
3
4
Order By: Relevance
“…TEA does not influence fibrinolytic activity in vein walls [3]. Therefore, neither our study nor previous studies [5,14,15,32] observed a greater incidence of venous thrombosis in patients treated with TEA. However, the detection of DVT in our patients was based on clinical observations (thigh/calf swelling [ 3 cm and calf tenderness), followed by positive findings of antegrade venography which did not reveal the true incidence of DVT.…”
Section: Discussioncontrasting
confidence: 46%
“…TEA does not influence fibrinolytic activity in vein walls [3]. Therefore, neither our study nor previous studies [5,14,15,32] observed a greater incidence of venous thrombosis in patients treated with TEA. However, the detection of DVT in our patients was based on clinical observations (thigh/calf swelling [ 3 cm and calf tenderness), followed by positive findings of antegrade venography which did not reveal the true incidence of DVT.…”
Section: Discussioncontrasting
confidence: 46%
“…The rationale for AKI = acute kidney injury; DVT = deep vein thrombosis; Hb = hemoglobin concentration; MI = myocardial infarction; PE = pulmonary embolism; RBC = red blood cells; THA = total hip arthroplasty; TKA = total knee arthroplasty; TXA = tranexamic acid utilizing the TXA dose was established independently in 2012 prior to initiation of the protocol following an extensive review of available literature by the Pharmacy and Therapeutics Committee. [2][3][4][5][6][9][10][11][14][15][16][17] It was determined that, from the highly variable dosing reported, this 20 mgÁkg -1 dose provided a balance between reducing perioperative blood loss and RBC transfusion while limiting the incidence of potential adverse events. Nevertheless, this study did not incorporate a well-defined a priori standardized intraoperative fluid management strategy with strictly defined transfusion triggers, which limited the interpretation of our data.…”
Section: Discussionmentioning
confidence: 99%
“…Méthode Nous avons mis en oeuvre une politique de qualité des soins afin de procéder à l'administration universelle de TXA par voie intraveineuse à une dose de 20 mgÁkg -1 à tous les patients admissibles subissant une arthroplastie totale de la hanche ou du genou entre le 21 Administration of tranexamic acid (TXA) has been shown to reduce blood loss and allogeneic red blood cell (RBC) transfusion in cardiac and various noncardiac surgical procedures. 1 Many randomized controlled trials, [2][3][4][5][6] systematic reviews, and meta-analyses [7][8][9][10][11] have shown that systemic and topically administered TXA reduces allogeneic RBC transfusion in hip or knee arthroplasty surgery. Recent observational studies have also shown an association between TXA use and reduced RBC transfusion.…”
Section: Résuméunclassified
“…Similarly, Kagoma et al [18], based on a meta-analysis of randomized trials among patients undergoing elective THR or TKA, reported antifibrinolytic agents reduce bleeding, reduce the risk of transfusion by almost 50%, and do not appear to increase the risk of venous thromboembolism. For patients undergoing primary hip replacement, Rajesparan et al [22] and Husted et al [17] previously reported tranexamic acid is cost-effective in reducing blood loss and transfusion requirements. Our data support the use of tranexamic acid in patients undergoing revision hip arthroplasty.…”
Section: Discussionmentioning
confidence: 99%